Film Grain‐Size Related Long‐Term Stability of Inverted Perovskite Solar Cells. Issue 18 (7th September 2016) - Chiang, Chien‐Hung; Wu, Chun‐Guey
Abstract: The power conversion efficiency (PCE) of the perovskite solar cell is high enough to be commercially viable. The next important issue is the stability of the device. This article discusses the effect of the perovskite grain‐size on the long‐term stability of inverted perovskite solar cells. Perovskite films composed of various sizes of grains were prepared by controlling the solvent annealing time. The grain‐size related stability of the inverted cells was investigated both in ambient atmosphere at relative humidity of approximately 30–40 % and in a nitrogen filled glove box (H2 O<0.1 ppm, O2 <10 ppm). The PCE of the solar cell based on a perovskite film having the grain size larger than 1 μm (D ‐10) decreases less than 10 % with storage in a glove box and less than 15 % when it was stored under an ambient atmosphere for 30 days. However, the cell using the perovskite film composed of small (∼100 nm) perovskite grains (D‐0) exhibits complete loss of PCE after storage under the ambient atmosphere for only 15 days and a PCE loss of up to 70 % with storage in the glove box for 30 days. These results suggest that, even under H2 O‐free conditions, the chemical‐ and thermal‐induced production of pin holes at the grain boundaries of the perovskite film could be the reason for long‐term instability of inverted perovskite solar cells. Abstract : Removing boundaries ! Inverted perovskite solar cells are fabricated from perovskite films with varied grain size. The films with larger grain size show improved stability under both glove‐box‐controlled and ambient conditions compared with the films having smaller grain size, suggesting that, the chemical‐ and thermal‐induced production of pin holes at grain boundaries could be the reason for long‐term instability of inverted perovskite solar cells.